Role of lubricin and boundary lubrication in the prevention of chondrocyte apoptosis - Waller, Kimberly A. (National Academy of Sciences, 2013)
Osteoarthritis is a complex disease involving the mechanical breakdown of articular cartilage in the presence of altered joint mechanics and chondrocyte death, but the connection between these factors is not well established. Lubricin, a mucinous glycoprotein encoded by the PRG4 gene, provides boundary lubrication in articular joints. Joint friction is elevated and accompanied by accelerated cartilage damage in humans and mice that have genetic deficiency of lubricin. Here, we investigated the relationship between coefficient of friction and chondrocyte death using ex vivo and in vitro measurements of friction and apoptosis. We observed increases in whole-joint friction and cellular apoptosis in lubricin knockout mice compared with wild-type mice. When we used an in vitro bovine explant cartilage-on-cartilage bearing system, we observed a direct correlation between coefficient of friction and chondrocyte apoptosis in the superficial layers of cartilage. In the bovine explant system, the addition of lubricin as a test lubricant significantly lowered the static coefficient of friction and number of apoptotic chondrocytes. These results demonstrate a direct connection between lubricin, boundary lubrication, and cell survival and suggest that supplementation of synovial fluid with lubricin may be an effective treatment to prevent cartilage deterioration in patients with genetic or acquired deficiency of lubricin.